2019
DOI: 10.1515/opag-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on the morphological, physiological and biochemical properties of lettuce (Lactuca sativa L.) in Bangladesh

Abstract: This study aimed to explore the changes in morphological, physiological and biochemical characteristics of lettuce (Lactuca sativa L.) in response to salt stress when grown using hydroponic techniques. The seedlings were subjected to five different concentrations (0 mM, 50 mM, 100 mM, 150 mM, and 200 mM) of NaCl for three weeks. During the salt stress, morphological properties (shoot length, root length, total plant weight, leaf number) were measured in every week. After 21 days of salt stress, physiological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
11
20
1
Order By: Relevance
“…ese damage effects induced by salt stress suppress the wheat shoot and root growth and therefore negatively affect FW and DW. Moreover, there was a progressive reduction in the wheat's FW and DW weights with increasing NaCl level, which was compatible with previous studies [1,22]. e minimum decrease in the FW and DW in Sakha69 cultivar International Journal of Agronomy might be due to the extraeffective detoxification mechanism, including the antioxidant defence mechanisms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…ese damage effects induced by salt stress suppress the wheat shoot and root growth and therefore negatively affect FW and DW. Moreover, there was a progressive reduction in the wheat's FW and DW weights with increasing NaCl level, which was compatible with previous studies [1,22]. e minimum decrease in the FW and DW in Sakha69 cultivar International Journal of Agronomy might be due to the extraeffective detoxification mechanism, including the antioxidant defence mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…e notable decreases were observed with Sakha8, which was the most influenced cultivar by saline conditions, followed by Giza168 and Sakha69 which was the most resistant cultivar to the NaCl salt application. e response of plant growth to salinity stress varies among species and has been reported in many investigations [1,2,5,21,22]. In this consideration, Bacu et al [7] demonstrated that an increase in salt concentration (50, 100, and 200 mM NaCl) induced a significant decrease in the growth criteria (shoot, root, and leaf length) of five wheat cultivars.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, studies about the effect of saline stress on the phenolic composition of lettuce have shown some conflicting results since there are diverse studies claiming increases in the phenolic composition and others that claim decreases in the levels of phenolic compounds because of saline stress. Some studies have reported that salinity can lead to non-significant changes if saline stress is low (NaCl concentration <100 mM ), or even to lower phenol index in lettuce leaves when high levels of salinity (150-1000 mM of NaCl) are used in growth media [5,36], thus, there could be a dose-dependent response. On the contrary, the results reported by Mahmoudi and co-workers [37] noted that lettuce can show different behaviors with regard to the accumulation of phenolic compounds depending not only on the lettuce variety but also on the type of salinity to which it is exposed [37].…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…It is traditionally consumed fresh, as in a Mediterranean diet. Lettuce stands out for its content of fiber, folate, vitamins, and bioactive compounds such as phenolic acids and flavonoids, mainly flavonols [1,2,5].…”
Section: Introductionmentioning
confidence: 99%